2022
DOI: 10.1093/icesjms/fsac167
|View full text |Cite
|
Sign up to set email alerts
|

Productivity, pressure, and new perspectives: impacts of the COVID-19 pandemic on marine early-career researchers

Abstract: The worldwide disruption caused by the beginning of the COVID-19 pandemic has dramatically impacted the activities of marine scientists working towards the goals of the UN Ocean Decade. As in other disciplines, marine early-career researchers (ECRs) are essential contributors to the development of novel and innovative science. Based on a survey of 322 of our peers, we show that the pandemic negatively impacted marine ECRs in ways that further exacerbate existing structural challenges such as social isolation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…As similar with Jackman et al (2022), more ECRs are working remotely due to the pandemic citing more disadvantages (e.g., more meetings, reduced quality of meetings, and distractions with home- and work-life) than advantages (e.g., more time from less commuting, more flexibility with workdays, and engaging with collaborators) although our participants expressed more disadvantages with remote meetings. Schadeberg et al (2022) also found remote work advantageous for some ECRs, specifically more time from less commuting and more flexibility with workdays.…”
Section: Summaries Of Resultsmentioning
confidence: 95%
“…As similar with Jackman et al (2022), more ECRs are working remotely due to the pandemic citing more disadvantages (e.g., more meetings, reduced quality of meetings, and distractions with home- and work-life) than advantages (e.g., more time from less commuting, more flexibility with workdays, and engaging with collaborators) although our participants expressed more disadvantages with remote meetings. Schadeberg et al (2022) also found remote work advantageous for some ECRs, specifically more time from less commuting and more flexibility with workdays.…”
Section: Summaries Of Resultsmentioning
confidence: 95%
“…This paper is based on an interactive session held at a conference in 2021 (Higino et al, 2021). By that time, we were about 18 months into the COVID-19 pandemic, which highly impacted the scientific career of ECRs (Corlett et al, 2020;Lokhtina et al, 2022;Schadeberg et al, 2022). In this context, we aimed at using speculative story making to outline our wishes for the future of (sub)tropical ecological research (Box 1; Supplementary Information).…”
Section: Introductionmentioning
confidence: 99%
“…Targeted actions and concerted efforts between academic institutions, funders, industry, decision-makers, the scientific community, and wider society, will be essential to supporting and empowering women ECRs. The COVID-19 pandemic has generated a strong bias against ECRs (Schadeberg et al, 2022), especially due to parenthood (Cardel et al, 2020a;Staniscuaski et al, 2021) and presents a window of opportunity to reflect on academic practices and cultures (Gibson et al, 2020;Keynejad et al, 2021). To date, the majority of related research and policy initiatives on gender inequality within academia have focused on how to better support women in Science, Technology, Engineering, and Mathematics (STEM; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Holzinger et al, 2018;Cardel et al, 2020a), particularly in marine science. In the marine context, previous research has focused on how to enable women scientists (Giakoumi et al, 2021;Shellock et al, 2022) or ECRs in marine science (Andrews et al, 2020;Brasier et al, 2020;Pardo et al, 2020;Schadeberg et al, 2022). But, research has not explored the intersection between gender and the early career stage.…”
Section: Introductionmentioning
confidence: 99%